Song Model Development For Character Education Elementary School Students (Jurnal Seni Musik, 2022)
The purpose of this research is to produce a collection of songs about character education for elementary school students, which contains discipline, mutual cooperation, honesty, responsibility, tolerance, cooperation, parental love, and love for the homeland. This research is a design and development research. Researchers developed a model that would produce model songs about character education for elementary school students. The steps of this research include identifying the need for pieces with the theme of discipline, cooperation, honesty, responsibility, tolerance, parental love, and love for the homeland used in learning in schools. Then proceed with prototypes of model songs with the theme of discipline, mutual cooperation, honesty, responsibility, tolerance, parental love, and love for the homeland. The end study is an expert assessment of the feasibility of the model songs that have been produced. This collection of model songs about character education is expected to be a teacher's handbook/reference in the learning process of arts and culture as well as other subjects with indicators of changing student attitudes and behavior. At the same time, it is an effort to improve the nation's character from an early age during the increasing number of juvenile delinquency cases. Result of the research that the song can improve the nation's character from an early age during the increasing number of juvenile delinquency cases.